Karakteristik Konsumen Oatside di Kota Bandung - Az-Zahra, Aliffah; Wiyono, Sulistyodewi Nur; Budiman, Muhammad Arief; Kusumo, Rani Andriani Budi (Universitas Galuh, 2024)
Agro-industry is growing rapidly along with changes in healthy lifestyles and environmental awareness in society. An example of an agro-industrial product is milk. However, cow's milk is lactose intolerant and has a negative environmental impact. From this problem, plant-based milk comes as a solution. Plant-based milk comes from plants, one of which is oat. The first oat milk to come to Asia is Oatside. Previous research says that when consumers are fully aware of the benefits of consuming Oatside, that is when they are interested and intend to buy the product. However, in fact, the benefits of Oatside are still not widely known by consumers. Thus, this study aims to determine how consumer characteristics, quality performance and brand image of Oatside brand oat milk in Bandung City so that producers can determine the next marketing strategy to increase product knowledge as well as Oatside consumption. The research method used is quantitative method. The technique used is purposive sampling with a size of 100 respondents. Variables were measured with a Likert Scale and processed with descriptive statistical analysis. The results showed that Oatside consumers in Bandung City are women, aged 17-25 years, have a bachelor's degree, students, have an income of < Rp1,500,000 and are not married. Consumers also rated the durability of Oatside products and brands as better than other indicators.